Associations between mindfulness and general change mechanisms in individual therapy: Secondary results of a randomised controlled trial. Issue 4 (20th May 2019) - D'Errico, Louisa; Call, Manuela; Blanck, Paul; Vonderlin, Eva; Bents, Hinrich; Mander, Johannes
Abstract: Objective: The aim of this study was to investigate the possible effects of the interactions between mindfulness‐based session introductions and general change mechanisms on outcome in cognitive behavioural therapy (CBT). Method: We investigated the effects of different session introductions on change mechanisms and their prediction of clinical outcome over the course of 25 sessions of training therapy. We compared session introductions with mindfulness (M) elements with progressive muscle relaxation (PMR) and treatment as usual (TAU) in routine CBT sessions conducted by therapists in training. Participants included 162 patients who were diagnosed primarily with either depression or anxiety disorder and 48 therapists. To address the nested data structure, we used multilevel models. Results: Multilevel modelling (MLM) indicated that the interaction between an increase in several general change mechanisms and treatment condition (TAU + M vs. TAU + PMR) on therapeutic outcome was significant. From the patient perspective, MLM indicated that only the interaction between an increase in one general change mechanism (clarification of meaning) and treatment condition (TAU + M vs. TAU + PMR) turned out significantly. From both perspectives, correlation analyses revealed that general change mechanism effects on outcome were stronger in TAU + M than in TAU + PMR. Conclusion: Mindfulness has an impact on general change mechanisms, especially for therapists. These associations lead to a significantly higher effect on outcome compared to introductions with PMR.